A functionalized ITO chip material and its application in mass spectrometry
By using functionalized ITO chip materials as nano substrates of SALDI-MS technology, the problems of matrix background peak interference and crystallization are solved, and efficient mass spectrometry analysis is achieved, especially suitable for the detection of small molecule compounds.
Patent Information
- Application Number
- CN202410230694.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-29
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-02-29
AI Technical Summary
In the existing mass spectrometry analysis technology, matrix background peaks are severely disturbed, uneven matrix crystallization leads to poor reproducibility and imaging artifacts, and the detection and identification of small molecule metabolites are hindered.
Using functionalized ITO chip material, which has surface nanostructure and excellent photothermal conversion efficiency, is used as a nano substrate in SALDI-MS technology, and the sample to be tested is directly added dropwise for mass spectrometry analysis.
The laser desorption/ionization efficiency is significantly improved, and the SALDI-MS spectrum formed has almost no background interference and a high signal-to-noise ratio. It is suitable for bipolar mass spectrometry detection and analysis of small molecular compounds with molecular weight less than 3000 Da.
Smart Images

Figure CN118156119B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of nanomaterials and mass spectrometry, and more specifically, to a functionalized ITO chip material and application thereof in mass spectrometry. Background Art
[0002] Matrix-assisted laser desorption / ionization mass spectrometry (MALDI-MS) technology is one of the most mainstream soft ionization mass spectrometry methods, but it is often interfered by serious matrix background peaks in the low mass number range (m / z <500), and the matrix crystallization is uneven, which easily leads to problems such as poor reproducibility and imaging artifacts (Anal. Chem., 2016, 88, 1734-1741). At the same time, although the use of organic matrix can improve the ionization efficiency of some metabolites, peptides and proteins, it also inevitably hinders the detection and identification of small molecule metabolites. With the rapid development of nanotechnology, substrates and nanomaterials with nanostructures have gradually developed. Since these nanomaterials can effectively absorb and locally enhance laser energy and then transfer it to the molecules to be tested, they partially solve the shortcomings of traditional matrices, such as spectral peak background interference and uneven matrix crystallization. However, in actual analysis, nanoparticles still need to be mixed with the sample to be tested before spotting, which limits the application of this technology in high-throughput mass spectrometry analysis.
[0003] For this reason, compared with inorganic nanoparticle materials, the surface-assisted laser desorption / ionization mass spectrometry (SALDI-MS) technology based on nano-based materials has shown unique analytical performance in the mass spectrometry analysis of small molecule compounds (Mass Spec. Rev., 2022, 41, 373-420; Adv. Funct. Mater., 2019, 29, 1903609.). Since the nano-based materials have the advantages of high specific surface area, high electrical conductivity, low thermal conductivity, and good light-to-heat conversion efficiency, the mass spectrometry sampling and analysis can be quickly performed by simply dropping the sample to be tested directly on the surface of the material, which greatly shortens the sample preparation time and provides the possibility for high-throughput mass spectrometry analysis. At present, most SALDI substrates are based on carbon materials (such as carbon nanotubes, graphene, graphene oxide, etc.) (Anal. Chem., 2010, 82, 6208-6214; ACS Nano, 2011, 5, 4550-4561), silicon materials (silicon dioxide nanowires, porous silica, silicon dioxide films, etc.) (Nature, 1999, 399, 243-246; Nature, 2007, 449, 1033-1036; ACS Nano, 2020, 14, 6785-6794) and titanium materials (titanium dioxide nanotubes, titanium dioxide nanowires, etc.) (Chem. Sci., 2017, 8, 3926; Anal. Chem., 2022, 94, 952-959), etc., which are opaque materials and are not compatible with subsequent optical staining imaging applications. At the same time, the preparation of the above materials often requires high temperature and high pressure, strong acids and alkalis, and even photolithography technology (ACS Appl. Mater. Interfaces, 2019, 11, 20509-20520, Adv. Funct. Mater., 2021, 31, 2102475). Not only is the preparation process cumbersome and has a long preparation cycle, but it is also expensive and difficult to meet the high-sensitivity detection and analysis of a wide variety of small molecule compounds in daily life. This limits the widespread application of SALDI-MS to a certain extent. Summary of the invention
[0004] The object of the present invention is to overcome the deficiencies of the prior art and provide a functionalized ITO chip material. The ITO chip material has both a surface nanostructure and excellent light-to-heat conversion efficiency. Compared with before the functionalization treatment, the chip material has a significantly improved desorption / ionization efficiency in laser desorption / ionization mass spectrometry (LDI-MS) analysis. It can be used as a nano-substrate for SALDI-MS technology, and the SALDI-MS spectrum formed has almost no background interference (m / z<500) and a high signal-to-noise ratio, and is suitable for bipolar mass spectrometry detection and analysis of small molecule compounds with a molecular weight of less than 3000Da.
[0005] Another object of the present invention is to provide a method for preparing the functionalized ITO chip material.
[0006] Another object of the present invention is to provide the application of the functionalized ITO chip material in SALDI-MS.
[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0008] A functionalized ITO chip material is prepared according to the following method:
[0009] S1. Place the ITO chip in a container, add an organic solvent and deionized water to form layers, with the upper layer being the aqueous phase and the lower layer being the organic phase;
[0010] S2. Add HCl solution to the upper aqueous phase to adjust the pH to 2-4, and inject tetramethylammonium tetrakis (4-chlorophenyl) borate dissolved in an organic solvent into the lower organic phase;
[0011] S3. adding the positively charged plasmon nanostructured material mixed with the organic solvent to the interface between the upper layer and the lower layer;
[0012] S4. respectively adding the COF precursor directly to the lower organic phase, reacting sufficiently to form a COF film loaded with the plasmonic nanostructure material at the interface between the upper and lower layers;
[0013] S5. Depositing the COF film on the surface of the ITO chip to obtain the functionalized ITO chip material;
[0014] The precursors of the COF are aldehyde-containing monomers with topological symmetry and amine-containing monomers with topological symmetry.
[0015] Since TMATPBCl can ionize anions and cations that are dissolved in the aqueous phase and the organic phase respectively, it is possible to adjust the potential difference between the two phases to promote the hydrogen ions in the aqueous phase to enter the organic phase, thereby catalyzing the condensation between the amino group and the aldehyde group of the COF precursor. The COF film formed by the reaction is attached to the pre-placed ITO chip by deposition to obtain the functionalized ITO chip. The functionalized ITO chip material has both surface nanostructure and excellent light-to-heat conversion efficiency, which can effectively avoid the problems of many background peaks of traditional organic matrices, uneven recrystallization, and easy imaging illusions.
[0016] Preferably, the organic solvent in S1 is one of 1,2-dichloroethane and chloroform. Specifically, the organic solvent is 1,2-dichloroethane.
[0017] Preferably, the pH value is adjusted to 3 in S2.
[0018] Preferably, the concentration of the TMATPBCl solution in S2 is 5-15 mM, specifically, the solution concentration is 10 mM.
[0019] Preferably, the organic solvent in S3 is soluble in the aqueous phase and the organic phase. Most preferably, the organic solvent is methanol.
[0020] Preferably, the plasmonic nanostructure material in S3 may be one or more of gold nanospheres, gold nanorods, gold nanostars, silver nanospheres, silver nanowires, silver nanosheets, silver nanocubes, platinum nanospheres, carbon quantum dots, and graphene nanosheets.
[0021] The positively charged modified plasmon nanostructure material can be prepared according to the prior art method. The positively charged modification makes the plasmon nanostructure material carry positive charges.
[0022] Preferably, the diameter distribution of the plasmon nanostructure material is 1 to 1000 nm; more preferably, the diameter distribution is 60 to 80 nm. Within this diameter range, the obtained plasmon nanostructure material has a good resonance enhancement effect at 355 nm.
[0023] Preferably, the plasmon nanostructure material is in the shape of any one of sphere, rod, star, line, porous or sheet, which is a nanostructure that can support plasmon resonance. Specifically, the shape is sphere.
[0024] More specifically, in S3, the most common plasmonic nanostructured material modified with positive charge is cysteamine-gold nanoparticles (Cys-Au NPs). Cysteamine has a thiol group at one end and an amino group at the other end. The thiol group is bound to the gold particles, and the amino group is easily bound to hydrogen ions, so that the surface of the cysteamine-gold nanoparticles is easily positively charged.
[0025] Preferably, the injection speed in S3 is 10-100 μL / min, specifically, the injection speed is 50 μL / min.
[0026] Preferably, the organic solvent in S4 is insoluble in water. Most preferably, the organic solvent is 1,2-dichloroethane.
[0027] Preferably, the aromatic aldehyde-containing monomer with topological symmetry in S4 is any one or more of trimesicaldehyde, 2,4,6-trihydroxy-1,3,5-benzenetricarbaldehyde, tris(4-formylbiphenyl)amine, tetrakis(4-formylphenyl)silane, 1,3,5-tris(4'-formyl[1,1'-biphenyl]-4-yl)benzene, tetrakis(4-formylphenyl)methane, 2,5-dichloroterephthalaldehyde, 4,4'-biphenyldicarboxaldehyde, 4,4'-dihydroxy-3,3'-glyoxalbiphenyl, 4,4-p-tetraphenyldicarboxaldehyde, 2,2'-bipyridine-4,4'-dicarboxaldehyde, 2,6-naphthalenedicarboxaldehyde or 2,5-dihydroxy-1,4-benzenedicarbaldehyde;
[0028] The aromatic amino-containing monomer with topological symmetry is any one or more of 5,5'-diamino-2,2'-bipyridine, p-diaminoazobenzene, p-phenylenediamine, 2,6-diaminoanthraquinone, 4,4'-diaminoterphenyl, 2,6-diaminoanthracene, 2,6-naphthalenediamine, 4,4,4"-triaminotriphenylmethane, tetrakis(4-aminophenyl)methane, 1,3,5-tris(4-aminophenyl)benzene, 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, 5,10,15,20-tetrakis(4-aminophenyl)porphyrin or 5,10,15,20-tetrakis(4-formaldehydephenyl)-21H,23H-porphyrin.
[0029] More preferably, the precursor of the COF is selected from 5,10,15,20-tetrakis(4-aminophenyl)porphyrin (Tph) and 2,5-dihydroxyterephthalaldehyde (Dha).
[0030] The concentration of the COF precursor is sufficient to form COF. When the COF precursor is selected from 5,10,15,20-tetrakis(4-aminophenyl)porphyrin (Tph) and 2,5-dihydroxyterephthalaldehyde (Dha), the concentration of 5,10,15,20-tetrakis(4-aminophenyl)porphyrin in S4 is preferably 0.1-0.5 mM; the concentration of 2,5-dihydroxyterephthalaldehyde is preferably 0.5-1.5 mM.
[0031] Preferably, the injection speed in S4 is 0.5-2 mL / min, specifically, the injection speed is 1 mL / min.
[0032] Preferably, the reaction time in S4 is 2 to 5 days, specifically, the reaction time is 3 days.
[0033] The following uses Cys-Au NPs as an example of a positively charged plasmonic nanostructured material to demonstrate its preparation method:
[0034] Preparation of Cys-Au NPs: 400 μL of 100-400 mM cysteine hydrochloride was mixed with 40 mL of 0.5-3 mM chloroauric acid aqueous solution, and stirred rapidly for 20 min at room temperature in the dark. Subsequently, 10 μL of 5-20 mM sodium borohydride was quickly added to the above reaction solution, and stirred vigorously for 15 min at room temperature in the dark to obtain Cys-AuNPs, which were stored at 4°C for future use.
[0035] More specifically, the parameters for preparing Cys-Au NPs are as follows: 400 μL of 213 mM cysteine hydrochloride is mixed with 40 mL of 1.42 mM chloroauric acid aqueous solution, and stirred rapidly for 20 min at room temperature and in the dark. Subsequently, 10 μL of 10 mM sodium borohydride is quickly added to the above reaction solution, and stirred vigorously for 15 min at room temperature and in the dark to obtain Cys-Au NPs, which are stored at 4°C for later use. After testing, the diameter distribution of Cys-Au NPs obtained under this condition is 60 to 80 nm.
[0036] In the present invention, TMATPBCl can be prepared by the following method:
[0037] Preparation of TMATPBCl: TMATPBCl is synthesized by substitution reaction of KTPBCl with a concentration of 0.1 to 0.5 mM and TMACl with a concentration of 4 to 10 mM in a mixed solvent of methanol and water, and then recrystallized with acetone and washed and dried.
[0038] More specifically, the parameters for preparing TMATPBCl are as follows: KTPBCl with a concentration of 0.3 mM and TMACl with a concentration of 6.6 mM undergo a replacement reaction in a mixed solvent of methanol and water to synthesize TMATPBCl, which is then recrystallized using acetone and washed and dried.
[0039] Application of the functionalized ITO chip material in mass spectrometry.
[0040] More preferably, the functionalized ITO chip material is used as a nano-substrate for mass spectrometry detection.
[0041] More specifically, the application is to directly drip a liquid containing the substance to be tested onto the functionalized ITO chip material, and after it dries, place the material onto a mass spectrometer target plate for subsequent direct laser desorption / ionization process and mass spectrometry detection.
[0042] The conditions for mass spectrometry detection can refer to the existing technology. Generally, laser is used to ablate and sample the residue of the object to be detected, and the mass spectrometer is used to detect the object to be detected to obtain the mass spectrum of the object to be detected.
[0043] The application scope is mass spectrometry analysis of small molecule compounds with a molecular weight less than 3000 Da.
[0044] In the present invention, the small molecule compound may exist in liquid residue, sediment, colloid and other substances.
[0045] The small molecule compounds of the present invention include, but are not limited to, amino acids, nucleosides, flavonoids, alkaloids, sugars, saturated and unsaturated fatty acids, dye drugs, polymers, pesticides and the like.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] The present invention provides a functionalized ITO chip material, which has nanoscale surface uniformity, high photothermal conversion efficiency and desorption / ionization efficiency. The functionalized ITO chip of the present invention does not require complicated tissue sample pretreatment or other organic matrix assistance when used as a substrate material for SALDI-MS for mass spectrometry analysis. The spectrum formed has almost no background interference and a high spectrum signal-to-noise ratio. It is perfectly compatible with subsequent tissue section staining and microscopic imaging, and can be applied to positive and negative ion detection modes at the same time, especially suitable for high-sensitivity detection of compounds with a molecular weight of less than 3000Da. The functionalized ITO chip material of the present invention has a simple preparation method and is easy to use. It can replace existing ITO materials and be used in commercialized MALDI-MS or LDI-MS instruments on the market, and has broad universality and commercialization prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 Schematic diagram of the synthesis of the functionalized ITO chip material of Example 1.
[0049] Figure 2 This is an electron microscope characterization image of the functionalized ITO chip material of Example 1.
[0050] Figure 3 This is the mass spectrum of a mixture of 15 amino acids directly analyzed from the functionalized ITO chip material in Example 1, where * indicates background interference peaks.
[0051] Figure 4 This is the mass spectrum of the mixed sample of four nucleosides directly analyzed from the functionalized ITO chip material in Example 1.
[0052] Figure 5This is the mass spectrum of the mixed sample of three flavonoids directly analyzed by the functionalized ITO chip material in Example 1.
[0053] Figure 6 This is the mass spectrum of a mixed sample of three alkaloids directly analyzed on the functionalized ITO chip material in Example 1.
[0054] Figure 7 This is the mass spectrum of a mixed sample of four sugars directly analyzed from the functionalized ITO chip material in Example 1.
[0055] Figure 8 This is the mass spectrum of two polymer mixed samples directly analyzed for the functionalized ITO chip material in Example 1.
[0056] Fig. 9 This is the mass spectrum of a mixed sample of 12 saturated fatty acids directly analyzed from the functionalized ITO chip material in Example 1.
[0057] Fig.10 This is the mass spectrum of a mixed sample of five unsaturated fatty acids directly analyzed from the functionalized ITO chip material in Example 1, where * indicates a background interference peak.
[0058] Fig.11 This is the mass spectrum of the functionalized ITO chip material of Example 1 used for a mixture of 10 pesticides, where * indicates background interference peak.
[0059] Fig.12 This is a quantitative linear result graph of the functionalized ITO chip material in Example 1 for three compounds: (A) cytidine, (B) histidine and (C) crystal violet.
[0060] Fig.13 This is a graph showing the reproducibility results of the functionalized ITO chip material in Example 1 for three compounds: (A) cytidine, (B) histidine, and (C) crystal violet, between points and between batches.
[0061] Fig.14 This is a comparison chart of the signal intensities of three compounds, (A, B) cytidine, (C, D) histidine, and (E, F) crystal violet, after the functionalized ITO chip material of Example 1 was placed for 150 days. The results were measured every 30 days. DETAILED DESCRIPTION
[0062] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0063] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0064] Example 1
[0065] A functionalized ITO chip material is prepared according to the following method:
[0066] S1. The ITO chip was ultrasonically cleaned with acetone, ethanol and water respectively, and then placed in a separatory funnel after drying. 70 mL of DCE and 100 mL of deionized water were added to form layers, with the upper layer being the aqueous phase and the lower layer being the organic phase;
[0067] S2. A 0.3 mM KTPBCl and a 6.6 mM TMACl were subjected to a replacement reaction in a methanol and water mixed solvent to synthesize TMATPBCl, which was recrystallized using acetone and washed and dried, and then dissolved in DCE to prepare a 10 mM TMATPBCl solution, and then 1 mol / L HCl solution was added to the upper aqueous phase described in S1 to adjust the pH value of the aqueous phase to 3, and 5 mL of the prepared TMATPBCl solution was injected into the lower DCE organic phase;
[0068] S3. Mix 400 μL of 213 mM cysteine hydrochloride with 40 mL of 1.42 mM chloroauric acid aqueous solution, and stir rapidly for 20 min at room temperature and in the dark. Subsequently, quickly add 10 μL of 10 mM sodium borohydride to the reaction solution, and stir vigorously for 15 min at room temperature and in the dark to obtain spherical Cys-AuNPs with a diameter distribution of 60 to 80 nm. Then, mix the spherical Cys-Au NPs with a diameter of 60 to 80 nm with methanol and inject them into the interface between the upper layer and the lower layer at a speed of 50 μL / min.
[0069] S4. Tph (concentration of 0.37 mM, volume of 30 mL) and Dha (concentration of 0.88 mM, volume of 5 mL) dissolved in DCE were injected into the lower DCE organic phase at a rate of 1 mL / min and reacted for 3 days;
[0070] S5. removing the reaction solution, and depositing a film on the surface of the ITO chip to obtain the functionalized ITO chip material (AuNP / Tph-Dha COF / ITO).
[0071] The parameters of S1. to S4. above can be adjusted without affecting the implementation of the solution of the present invention. The performance of the obtained functionalized ITO chip is similar to that of Example 1.
[0072] Example 2
[0073] A functionalized ITO chip material is prepared according to the following method:
[0074] S1. The ITO chip was ultrasonically cleaned with acetone, ethanol and water respectively, and then placed in a separatory funnel after drying. 70 mL of DCE and 100 mL of deionized water were added to form layers, with the upper layer being the aqueous phase and the lower layer being the organic phase;
[0075] S2. A 0.3 mM KTPBCl and a 6.6 mM TMACl were subjected to a replacement reaction in a methanol and water mixed solvent to synthesize TMATPBCl, which was recrystallized using acetone and washed and dried, and then dissolved in DCE to prepare a 10 mM TMATPBCl solution, and then 1 mol / L HCl solution was added to the upper aqueous phase described in S1 to adjust the pH value of the aqueous phase to 3, and 5 mL of the prepared TMATPBCl solution was injected into the lower DCE organic phase;
[0076] S3. Cysteine-modified gold nanorods (Cys-Au NRs) with a diameter distribution of 60 to 80 nm were mixed with methanol and injected into the interface between the upper and lower layers at a speed of 50 μL / min;
[0077] S4. Tph (concentration of 0.37 mM, volume of 30 mL) and Dha (concentration of 0.88 mM, volume of 5 mL) dissolved in DCE were injected into the lower DCE organic phase at a rate of 1 mL / min and reacted for 3 days;
[0078] S5. removing the reaction solution, and depositing a film on the surface of the ITO chip to obtain the functionalized ITO chip material (AuNR / Tph-Dha COF / ITO).
[0079] The parameters of S1. to S4. above can be adjusted without affecting the implementation of the solution of the present invention. The performance of the obtained functionalized ITO chip is similar to that of Example 1.
[0080] Example 3
[0081] A functionalized ITO chip material is prepared according to the following method:
[0082] S1. The ITO chip was ultrasonically cleaned with acetone, ethanol and water respectively, and then placed in a separatory funnel after drying. 70 mL of DCE and 100 mL of deionized water were added to form layers, with the upper layer being the aqueous phase and the lower layer being the organic phase;
[0083] S2. A 0.3 mM KTPBCl and a 6.6 mM TMACl were subjected to a replacement reaction in a methanol and water mixed solvent to synthesize TMATPBCl, which was recrystallized using acetone and washed and dried, and then dissolved in DCE to prepare a 10 mM TMATPBCl solution, and then 1 mol / L HCl solution was added to the upper aqueous phase described in S1 to adjust the pH value of the aqueous phase to 3, and 5 mL of the prepared TMATPBCl solution was injected into the lower DCE organic phase;
[0084] S3. Cysteine-modified silver nanospheres (Cys-Ag NPs) with a diameter distribution of 60 to 80 nm were mixed with methanol and injected into the interface between the upper and lower layers at a speed of 50 μL / min;
[0085] S4. Tph (concentration of 0.37 mM, volume of 30 mL) and Dha (concentration of 0.88 mM, volume of 5 mL) dissolved in DCE were injected into the lower DCE organic phase at a rate of 1 mL / min and reacted for 3 days;
[0086] S5. removing the reaction solution, and depositing a film on the surface of the ITO chip to obtain the functionalized ITO chip material (AgNP / Tph-Dha COF / ITO).
[0087] The parameters of S1. to S4. above can be adjusted without affecting the implementation of the solution of the present invention. The performance of the obtained functionalized ITO chip is similar to that of Example 1.
[0088] Example 4
[0089] A functionalized ITO chip material is prepared according to the following method:
[0090] S1. The ITO chip was ultrasonically cleaned with acetone, ethanol and water respectively, and then placed in a separatory funnel after drying. 70 mL of DCE and 100 mL of deionized water were added to form layers, with the upper layer being the aqueous phase and the lower layer being the organic phase;
[0091] S2. A 0.3 mM KTPBCl and a 6.6 mM TMACl were subjected to a replacement reaction in a methanol and water mixed solvent to synthesize TMATPBCl, which was recrystallized using acetone and washed and dried, and then dissolved in DCE to prepare a 10 mM TMATPBCl solution, and then 1 mol / L HCl solution was added to the upper aqueous phase described in S1 to adjust the pH value of the aqueous phase to 3, and 5 mL of the prepared TMATPBCl solution was injected into the lower DCE organic phase;
[0092] S3. Cysteine-modified silver nanowires (Cys-Ag NWs) with a diameter distribution of 60 to 80 nm were mixed with methanol and injected into the interface between the upper and lower layers at a speed of 50 μL / min;
[0093] S4. Tph (concentration of 0.37 mM, volume of 30 mL) and Dha (concentration of 0.88 mM, volume of 5 mL) dissolved in DCE were injected into the lower DCE organic phase at a rate of 1 mL / min and reacted for 3 days;
[0094] S5. removing the reaction solution, and depositing a film on the surface of the ITO chip to obtain the functionalized ITO chip material (AgNW / Tph-Dha COF / ITO).
[0095] The parameters of S1. to S4. above can be adjusted without affecting the implementation of the solution of the present invention. The performance of the obtained functionalized ITO chip is similar to that of Example 1.
[0096] Performance Testing
[0097] (1) Electron microscopy characterization of functionalized ITO chips
[0098] The functionalized ITO chip prepared in Example 1 was analyzed by electron microscope scanning. Figure 2 As shown in the electron microscope image, it can be seen that the Tph-Dha COF film can be smoothly self-assembled on the ITO glass slide, and AuNPs can be evenly spread on the Tph-Dha COF / ITO surface, so that the functionalized ITO chip material has the advantages of high specific surface area, high electrical conductivity and low thermal conductivity, and good light-heat conversion efficiency.
[0099] The following tests all used the functionalized ITO chip prepared in Example 1.
[0100] (2) Functionalized ITO chips are used to detect and analyze small molecule compounds with a molecular weight less than 3000 Da
[0101] Amino acid detection: The functionalized ITO chip was used as the substrate material for SALDI-MS. A total of 15 mixed samples with a concentration of 1 mM, including γ-aminobutyric acid (GABA), alanine (Ala), proline (Pro), threonine (Thr), serine (Ser), valine (Val), methionine (Met), leucine (Leu), histidine (His), lysine (Lys), arginine (Arg), phenylalanine (Phe), tyrosine (Tyr), and tryptophan (Trp), were added to the functionalized ITO chip and then detected in the positive ion mode. The results are shown in the figure. Figure 3It can be found that there is almost no background interference in the mass spectrum and the spectrum signal-to-noise ratio is high, indicating that the functionalized ITO chip can be used as a SALDI-MS substrate material for the analysis of small molecule amino acid mixed samples in the positive ion mode.
[0102] Nucleoside sample detection: The functionalized ITO chip was used as the substrate material for SALDI-MS. Four mixed nucleoside samples, including cytidine, uridine, adenosine and guanosine, with a concentration of 1 mM were dripped onto the functionalized ITO chip and then detected in the positive ion mode. The results are as follows: Figure 4 It can be found that there is almost no background interference in the spectrum and the spectrum signal-to-noise ratio is high, indicating that the functionalized ITO chip can be used as a SALDI-MS substrate material for the analysis of mixed nucleoside samples in the positive ion mode.
[0103] Flavonoid sample detection: The functionalized ITO chip was used as the substrate material for SALDI-MS. Three flavonoid samples, Ginkgolide A, Ginkgolide B, and Ginkgetin, were added dropwise on the functionalized ITO chip at a concentration of 1 mM. The samples were then detected in the positive ion mode. The results are shown in Figure 2. Figure 5 It can be found that there is almost no background interference in the spectrum and the spectrum signal-to-noise ratio is high, indicating that the functionalized ITO chip can be used as a SALDI-MS substrate material for the analysis of flavonoid samples in the positive ion mode.
[0104] Alkaloid sample detection: The functionalized ITO chip was used as the substrate material for SALDI-MS. Catharanthine, Vinpocetine, and Vinblastine, three alkaloid samples with a concentration of 1 mM, were added to the functionalized ITO chip and then detected in the positive ion mode. The results are as follows: Figure 6 It can be found that there is almost no background interference in the spectrum and the spectrum signal-to-noise ratio is high, indicating that the functionalized ITO chip can be used as a SALDI-MS substrate material for the analysis of alkaloid samples in the positive ion mode.
[0105] Sugar sample detection: The functionalized ITO chip was used as the substrate material for SALDI-MS. Four sugar samples, including xylose, glucose, sucrose, and raffinose, with a concentration of 1 mM were added to the functionalized ITO chip, and then detected in the positive ion mode. The results are as follows: Figure 7It can be found that there is almost no background interference in the spectrum and the spectrum signal-to-noise ratio is high, indicating that the functionalized ITO chip can be used as a SALDI-MS substrate material for the analysis of sugar samples in the positive ion mode.
[0106] Polymer sample detection: The functionalized ITO chip was used as the substrate material for SALDI-MS. Two polymer samples, polyethylene glycol 600 (PEG600) and polyethylene glycol 2000 (PEG2000), were added to the functionalized ITO chip at a concentration of 1 mM each. The samples were then detected in the positive ion mode. The results are shown in Figure 2. Figure 8 It can be found that there is almost no background interference in the spectrum and the spectrum signal-to-noise ratio is high, indicating that the functionalized ITO chip can be used as a SALDI-MS substrate material for the analysis of polymer samples in the positive ion mode.
[0107] Detection of mixed saturated fatty acid samples: The functionalized ITO chip was used as the substrate material for SALDI-MS. A mixed sample of 12 saturated fatty acids, including dodecanoic acid (C12), tridecanoic acid (C13), tetradecanoic acid (C14), pentadecanoic acid (C15), palmitic acid (C16), heptadecanoic acid (C17), stearic acid (C18), nonadecanoic acid (C19), arachidic acid (C20), heneicosanoic acid (C21), docosanoic acid (C22), and tetracosanoic acid (C24), with a concentration of 1 mM was added to the functionalized ITO chip. The sample was then tested in the negative ion mode. The results are shown in Figure 2. Fig. 9 It can be found that there is almost no background interference in the spectrum and the spectrum signal-to-noise ratio is high, indicating that the functionalized ITO chip can be used as a SALDI-MS substrate material for the analysis of saturated fatty acid mixed samples in negative ion mode.
[0108] Unsaturated fatty acid mixed sample detection: The functionalized ITO chip was used as the substrate material for SALDI-MS. Five unsaturated fatty acid mixed samples with a concentration of 1 mM, including heptadecaenoic acid (C17:1), oleic acid (C18:1), arachidic acid (C20:1), erucic acid (C22:1), and tetracosenoic acid (C24:1), were added to the functionalized ITO chip. The samples were then tested in negative ion mode. The results are shown in Figure 2. Fig.10 It can be found that there is almost no background interference in the spectrum and the spectrum signal-to-noise ratio is high, indicating that the functionalized ITO chip can be used as a SALDI-MS substrate material for the analysis of unsaturated fatty acid mixed samples in negative ion mode.
[0109] Mixed pesticide detection: The functionalized ITO chip was used as the substrate material for SALDI-MS. A mixture of 10 pesticides, including glyphosate, pymetrozine, dinotefuran, imidacloprid, thiamethoxan, rotenone, isopropyloxalate, cyantraniliprole, chlorantraniliprole, and abamectin, with a concentration of 1 mM was added to the functionalized ITO chip and detected in the positive ion mode. The results are shown in the figure. Fig.11 It can be found that when the functionalized ITO chip is used as the SALDI-MS substrate, all 10 mixed pesticides can be detected, indicating that the functionalized ITO chip material has broad application prospects and universality.
[0110] (3) Detection sensitivity test of functionalized ITO chip
[0111] The functionalized ITO chip was used as the substrate material for SALDI-MS to quantitatively analyze three compounds, (A) cytidine, (B) histidine, and (C) crystal violet, in the positive ion mode. The test method was the same as the above-mentioned small molecule compound detection method. The results are shown in Figure 2. Fig.12 As shown in the figure, it can be seen that the detection limits (LODs, S / N≥6) of the functionalized ITO chip for the three compounds are 500amol, 72fmol and 100amol, respectively, indicating that the functionalized ITO chip has high detection sensitivity.
[0112] (4) Reproducibility of functionalized ITO chip surface
[0113] The functionalized ITO chip was used as the substrate material for SALDI-MS to detect three compound samples: (A) cytidine, (B) histidine, and (C) crystal violet. The test method was the same as the above-mentioned small molecule compound detection method. The results are shown in Figure 2. Fig.13 As shown, it can be found that the reproducibility of the three compounds between points and batches is good, and the relative standard deviation is less than 5%.
[0114] (5) Functionalized ITO chip stability test
[0115] After 150 days of storage, the functionalized ITO chip was used as the substrate material for SALDI-MS to detect the signal intensity of three compounds: (A, B) cytidine, (C, D) histidine, and (E, F) crystal violet (measured every 30 days). The test method was the same as the above-mentioned small molecule compound detection method. The results are shown in Fig.14 As shown, it can be found that the functionalized ITO chip material can be stored for a long time without affecting its sensitivity to small molecule mass spectrometry detection.
[0116] The performance test results of the functionalized ITO chips prepared in Examples 2 to 4 are similar to those of the functionalized ITO chip prepared in Example 1, and are also applicable to SALDI-MS positive and negative ion detection modes, and are suitable for high-sensitivity detection of compounds with a molecular weight of less than 3000 Da.
[0117] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A functionalized ITO chip material, characterized in that: Prepared as follows: S1. Place the ITO chip in a container, add an organic solvent and deionized water to form a layer, the upper layer is an aqueous phase, and the lower layer is an organic phase; S2. Add HCl solution to the upper aqueous phase to adjust the pH to 2-4, and inject tetramethylammonium tetrakis (4-chlorophenyl) borate dissolved in an organic solvent into the lower organic phase; S3. adding the positively charged plasmon nanostructured material mixed with the organic solvent to the interface between the upper layer and the lower layer; S4. respectively adding the COF precursor directly to the lower organic phase, reacting sufficiently to form a COF film loaded with the plasmonic nanostructure material at the interface between the upper and lower layers; S5. Depositing the COF film on the surface of the ITO chip to obtain the functionalized ITO chip material; The precursors of the COF are aldehyde-containing monomers with topological symmetry and amine-containing monomers with topological symmetry.
2. The functionalized ITO chip material according to claim 1, characterized in that: In S2, the concentration of the tetramethylammonium tetrakis(4-chlorophenyl)borate solution is 5 to 15 mM.
3. The functionalized ITO chip material according to claim 1, characterized in that: In S3, the diameter distribution of the plasmon nanostructure material is 1 to 1000 nm.
4. The functionalized ITO chip material according to claim 1, characterized in that: In S3, the shape of the plasmon nanostructure material is any one of spherical, rod-shaped, star-shaped, linear, porous, block-shaped, dot-shaped or sheet-shaped.
5. The functionalized ITO chip material according to claim 1, 3 or 4, characterized in that: In S3, the plasmonic nanostructure material is one or more of gold nanospheres, gold nanorods, gold nanostars, silver nanospheres, silver nanowires, silver nanosheets, silver nanocubes, platinum nanospheres, carbon quantum dots or graphene nanosheets.
6. The functionalized ITO chip material according to claim 1, characterized in that: In S3, the adding method is injection, and the injection speed is 10 to 100 μL / min.
7. The functionalized ITO chip material according to claim 1, characterized in that: The aromatic aldehyde-containing monomer with topological symmetry described in S4 is any one or more of trimesicaldehyde, 2,4,6-trihydroxy-1,3,5-benzenetricarbaldehyde, tris(4-formylbiphenyl)amine, tetrakis(4-formylphenyl)silane, 1,3,5-tris(4'-formyl[1,1'-biphenyl]-4-yl)benzene, tetrakis(4-formylphenyl)methane, 2,5-dichloroterephthalaldehyde, 4,4'-biphenyldicarboxaldehyde, 4,4'-dihydroxy-3,3'-glyoxalbiphenyl, 4,4-p-tetraphenyldicarboxaldehyde, 2,2'-bipyridine-4,4'-dicarboxaldehyde, 2,6-naphthalenedicarboxaldehyde or 2,5-dihydroxy-1,4-benzenedicarbaldehyde; The aromatic amino-containing monomer with topological symmetry is any one or more of 5,5'-diamino-2,2'-bipyridine, p-diaminoazobenzene, p-phenylenediamine, 2,6-diaminoanthraquinone, 4,4'-diaminoterphenyl, 2,6-diaminoanthracene, 2,6-naphthalenediamine, 4,4,4"-triaminotriphenylmethane, tetrakis(4-aminophenyl)methane, 1,3,5-tris(4-aminophenyl)benzene, 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, 5,10,15,20-tetrakis(4-aminophenyl)porphyrin or 5,10,15,20-tetrakis(4-formaldehydephenyl)-21H,23H-porphyrin.
8. The functionalized ITO chip material according to claim 1, characterized in that: The reaction time in S4 is 2 to 5 days.
9. Use of the functionalized ITO chip material according to any one of claims 1 to 8 in mass spectrometry.
10. The use according to claim 9, characterized in that: The application scope is mass spectrometry analysis of small molecule compounds with a molecular weight less than 3000 Da.
Citation Information
Patent Citations
Imprinting mass spectrometry imaging method based on titanium dioxide nanotube
CN114894882A
KR1017134800000B1